Evaluation of Hydrated Lime Filler in Asphalt Mixtures - Hasan Al-Jumaily, Mohammed Abbas (Al-Khwarizmi Engineering Journal, 2008)
Mineral filler is one of important materials and affecting on properties and quality of asphalt mixtures .There are different types of mineral filler depended on cost and quality , the matter encourages us to achieve this study to evaluate hydrated lime filler effects on properties of asphalt mixes related with strength and durability. Conventional asphaltic concrete mixtures with Portland cement and soft sandstone fillers and mixtures modified with hydrated lime were evaluated for their fundamental engineering properties as defined by Marshall properties , index of retained strength , indirect tensile strength , permanent deformation characteristics , and fatigue resistance .A typical dense graded mixture employed in construction of surface course pavement in Iraq in accordance with SCRB specifications was used .The materials used in this study included mineral aggregate materials (coarse and fine sizes) were originally obtained from Najaf Sea quarries and two grades of asphalt cements produced from Daurah refinery which are D47 and D66 . The physical properties , stiffness modulus and chemical composition are evaluated for the recovered asphalt cement from prepared asphalt mixes containing various filler types .The paper results indicated that the addition of hydrated lime as mineral filler improved the permanent deformation characteristics and fatigue life and the use of hydrated lime will decrease the moisture susceptibility of the asphalt mixtures.